2016
DOI: 10.7448/ias.19.4.20939
|View full text |Cite
|
Sign up to set email alerts
|

From conflict to partnership: growing collaboration between police and NGOs in countries with concentrated epidemics among key populations

Abstract: IntroductionBetween September 2012 and December 2015, a series of national and regional consultations, aimed at resolving a persistent dynamic of conflict between law enforcement agencies (LEAs) and civil society organizations (CSOs) working on issues of access to HIV services in high-priority countries for people who use drugs have been organized by the HIV/AIDS Section of the United Nations Office on Drugs and Crime, the Joint United Nations Programme on HIV/AIDS, the Law Enforcement and HIV Network (LEAHN) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
2
0
1
Order By: Relevance
“…However, access to services after violence is often complex due to the prevailing legal context [ 5 ]. Organised engagement of law enforcement agencies and CSOs could reduce the tensions between service providers and law enforcement and enhance partnerships to improve service delivery to high risk marginalised populations including FSWs [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, access to services after violence is often complex due to the prevailing legal context [ 5 ]. Organised engagement of law enforcement agencies and CSOs could reduce the tensions between service providers and law enforcement and enhance partnerships to improve service delivery to high risk marginalised populations including FSWs [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hal yang penting juga dalam hal ini adalah upaya melakukan pelayanan kolaboratif antara HIV AIDS, Tuberkullosis/TB dan Malaria. 14 Namun, untuk sarana dan pra sarana di lapangan, masih terdapat kekurangan, misalnya rusaknya mesin CD 4 yang belum diperbaiki karena kurangnya dana yang ada. Ketersediaan sumber daya, baik itu alat, uang maupun faktor pendukung lain adalah hal yang mempengaruhi baik buruknya implementasi dari suatu kebijakan/program di suatu organisasi.…”
Section: Aspek Akseptabilitas/penerimaanunclassified
“…The Poro Sapot project in Papua New Guinea worked to reduce the harassment of men who have sex with men and sex workers through training and sensitization of police at multiple levels [25]. Thomson et al have reported on a series of joint workshops between police and KAPS supported by the UN Office on Drugs and Crime (UNODC), contributing to the evidence that contact between police and KAPs outside the usual situations of conflict can be effective in rehumanizing each to the other [26]. This aligns with the evidence about what works in stigma reduction, with four approaches necessary and effective: information-based approaches, skills building, counselling and support and contact with affected groups [27].…”
Section: The Evidence For Police Engagementmentioning
confidence: 99%